Avaliação da efetividade dos medicamentos biológicos para o tratamento da Artrite Reumatoide - Jessica Barreto dos Santos (2015)
Rheumatoid arthritis (RA) is a systemic, chronic and progressive inflammatory disease which affects the synovial membrane of joints. The treatment of RA consists to educate the patient and his family, drug therapy, physiotherapy, psychosocial support, occupational therapy and surgical approaches.Treatment of RA includes non-steroidal anti-inflammatory, corticoids and synthetic (sDMARD) and biological (bDMARD) disease-modifying antirheumatic drugs. In this study we evaluated the effectiveness of bDMARD for the treatment of RA, through a systematic review and meta-analysis and an open prospective cohort study in Public Health System (SUS). In the systematic review was performed a search of cohort studies of patients with RA treated with bDMARD. The effectiveness evaluation criteria included the European League Against Rheumatism, the American College of Rheumatology, the Simplified Disease Activity Index, Clinical Disease Activity Index (CDAI), Disease Activity Score and the Health Assessment Questionnaire. In that study, adalimumab and etanercept were more effective than infliximab for naive patients. Furthermore, it was found that the bDMARD had better efficacy when combined with methotrexate than when alone. However, in cases of therapeutic failure to anti-TNF, rituximab and abatacept (non-anti-TNF) and etanercept (as a second anti-TNF) were more effective. However, more studies were found to rituximab, which reinforces the need for further studies regarding the effectiveness of these drugs. An open prospective cohort study (which is a part of this work) included individuals diagnosed with RA treated with anti-TNF adalimumab and etanercept in SUS, Brazil. The CDAI was considered to evaluate the effectiveness of the adalimumab and etanercept, comparing its measurements in three stages (first and second, second and third and first and third interviews). The drugs adalimumab and etanercept significantly reduced disease activity measured by CDAI in six and 12 months, however, no significant differences were observed between them. The percentage of patients that achieved remission or low disease activity was 46.7%. In a real-life scenario, the bDMARD are effective alternatives for RA treatment, as can be seen in the systematic review and cohort. In the systematic review, the bDMARD when used in combination with sDMARD showed better results than monotherapy. In the cohort, half of RA patients achieved the treatment target (remission or low disease activity). The others patients did not achieve remission or low disease activity and should have changed their medication, as directed by the Clinical Protocol and Therapeutic Guidelines of RA. In this case, continuous pharmaco-therapeutic monitoring performed by a multidisciplinary team could achieve better results, assuring the quality of use of the bDMARD.